1999
DOI: 10.1097/00005373-199911000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Obstruction Secondary to Enteral Feedings in Burn Trauma Patients

Abstract: Bowel obstruction, ischemic necrosis, or both, secondary to early and aggressive nutrition with a fiber supplemented enteral feeding is an uncommon, life-threatening complication. Understanding and early recognition of this potential complication are essential to prevention or successful treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(34 citation statements)
references
References 19 publications
0
32
0
2
Order By: Relevance
“…Some researchers have shown that the insoluble fibers may not reduce the occurrence of diarrhea. Besides, a few cases of intestinal obstruction have been reported in patients received insoluble fibers ( 2 , 20 ). One study compared the effect of enteral formula with and without soluble fiber and concluded that diarrhea episodes were significantly decreased in the patients received fiber containing formula ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…Some researchers have shown that the insoluble fibers may not reduce the occurrence of diarrhea. Besides, a few cases of intestinal obstruction have been reported in patients received insoluble fibers ( 2 , 20 ). One study compared the effect of enteral formula with and without soluble fiber and concluded that diarrhea episodes were significantly decreased in the patients received fiber containing formula ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…EN provides a complete nutrition with a low complication rate, good acceptance by the patient and favorable cost-effectiveness. 6 11 By delivering enteral feeding in the small bowel below the pylorus, the frequency of regurgitation and the risk of aspiration pneumonia are decreased. At the same time, nutrient intake is maximized with an increase in proteins and calories delivered and a shorter time to target the optimal dose of nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Though EN intolerance is not uncommon in the critically injured, failure to recognize such intolerance may result in the rare but devastating complication of nonocclusive bowel necrosis. The documented incidence ranges from 0.3% to 8.5%, with a mortality frequently in excess of 50% 31 , 34 36 . The precise etiology of nonocclusive bowel necrosis remains unclear; however, its consistent association with EN implicates the inappropriate administration of nutrients into a dysfunctional gastrointestinal tract.…”
Section: Enmentioning
confidence: 99%